Soluble yerba mate (Ilex Paraguariensis) extract enhances in vitro osteoblastic differentiation of bone marrow-derived mesenchymal stromal cells - Balera Brito, Victor Gustavo; Chaves-Neto, Antonio Hernandes [UNESP]; Landim de Barros, Thamine; Oliveira, Sandra Helena Penha de [UNESP] (Elsevier, 2019)
ETHNOPHARMACOLOGICAL RELEVANCE: Yerba mate (Ilex paraguariensis) consumption has been associated with beneficial effects on bone health. AIM OF THE STUDY: The purpose of this study was to evaluate the mechanism by which soluble yerba mate (SYM) stimulates osteoblast differentiation of bone marrow-derived mesenchymal stromal cells (BM-MSCs). MATERIALS AND METHODS: BM-MSCs from male Wistar rats were induced towards osteoblastic differentiation with different concentrations of SYM (10, 20, and 50 μg/mL). Osteoblastic differentiation was evaluated by measuring proliferation rates, alkaline phosphatase activity, MMP-2 activity, mineralization, and gene expression of Runx2, Osterix, β-catenin (Catnb), collagen type I (Col1a1), osteopontin (Opn), osteocalcin (Ocn), bone sialoprotein (Bsp), bone morphogenetic protein-2 (Bmp2), osteoprotegerin (Opg), and Rankl. We also analyzed cytokine production and MAP kinase pathways. RESULTS: SYM (10 μg/mL) did not show a cytotoxic effect and induced a slight increase in ALP activity; however, a great increase in mineralization was observed. SYM was also able to reduce TNF-α and IL-10 production; increase the expression of transcription factors Runx2, Osterix, and Catnb; and increase matrix proteins Opn, Bsp, Ocn, and Bmp2. We also observed a decrease in intracellular signaling of ERK, JNK, and p38 MAPK, which seemed to be related to the SYM response. CONCLUSIONS: Together, these results help to explain the promoting effect on osteoblast differentiation produced by a low SYM concentration. However, a higher SYM concentration presented deleterious effects, including cytotoxicity, decreased ALP activity, increased cytokine production, decreased bone marker gene expression, increased MAPK signaling, and significant mineralization reduction. In conclusion, our results suggest a concentration-specific direct stimulatory effect of SYM on osteoblastic differentiation in vitro.
Keywords: Bone marrow-derived mesenchymal stromal cells; Ilex paraguariensis; Osteoblast differentiation; Soluble yerba mate